Apolipoproteins, Triglycerides and Cholesterol - Waisundara, Viduranga Y.; Jovandaric, Miljana Z. (IntechOpen, 2020)
Lipids are one of the most important biomolecules and, given their relationship with several non-communicable diseases at large, this makes them significant to be studied both biochemically and clinically. As the title of the book suggests, apolipoproteins, triglycerides, and cholesterol are focused herein with fresh perspectives and novel insights, while certain overlooked areas are given their due attention. Although these three terms are very broad, the book aims at primarily serving as an update to existing knowledge. It is hoped that the readers will benefit from this book in advancing their understanding about the biochemical pathways, clinical applications, and remedial action in terms of ensuring health and wellbeing, as well as in identifying gaps that would help set the directions of scientific investigations in the future.